Determination of heavy metals in eggs of Little Grebe (Tachybaptus ruficollis) around the wastewater treatment ponds, Khon Kaen University. Issue 2 (17th February 2018) - Thongcharoen, Kanokporn; Robson, Mark G.; Keithmaleesatti, Sarun
ABSTRACT: Bird eggs can often be used as a bioindicator of potential effects in environment pollutions. Little Grebe ( Tachybaptus ruficollis ) lays the eggs around wastewater treatment ponds, Khon Kaen University. The aim of this study is to determine the contamination level of Hg, Pb, Cd, Cr, and Cu in egg content, eggshell and to relate hatching success. Fifteen eggs, four sludge samples, and wastewater samples were collected during September 2016 to April 2017 and were digested and determined using ICP-MS. Clutch size was 1–6 eggs and the weight, width, and length of eggs (mean ± SD) were 11.64 ± 0.91 g., 24.96 ± 0.85 mm, 35.05 ± 1.32 mm, respectively. Hatching success ( n = 15) was 96.7%. Cu and Pb were detected at low level in wastewater, and five heavy metals were contaminated in sludge samples. Cu> Cr> Pb> Hg were detected in egg samples ( n = 15), and all concentrations in egg content were more than in eggshell. Cr, Cu, Pb, and Hg concentration were not correlated between eggshell and egg content. This study indicated that the heavy metals can be contaminated in sediment, wastewater and can be transferred to egg of Little Grebes. These suggest the ecological risk of heavy metals on other long-living vertebrates living in the area.